Paradygmat według koncepcji Thomasa Samuela Kuhna. Analiza metodologicznoprawna - Chrząszcz, Bartosz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2021)
AbstractThe issue of the scientific paradigm invariably dominates in considerations devoted to science, its history, philosophy, as well as other detailed issues related to specific disciplines of knowledge. Thomas Samuel Kuhn, as a representative of the scientific community, noticed the shortcomings of the research approach, resulting mainly from cumulativism. The concept developed by him revolutionized many spheres of scientific activity, and the paradigm – newly defined and supplemented with a complex reflection on the processes taking place in science – is to this day a source of numerous discussions among researchers. The article aims to present the perception of the paradigm in the world of science, and todetermine to what extent the conclusions resulting from the concept outlined by Thomas Samuel Kuhn are significant from the methodological perspective.
Keywords: Kuhn, Thomas Samuel; the scientific paradigm; legal science; methodology